The Impact of Chronic Pain on Brain Structure and Connectivity - Manzoor Hussain, Mumahmmad Sajjad, Aqeel Ahmad, Hamidullah, Shah Muhammad Khan, Amjad Ali (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Chronic pain is now understood as more than a symptom; it can reshape mood, thinking, and even the physical layout of the brain. New imaging techniques are beginning to link extended pain with visible differences in brain size and the way its regions communicate. The current study examines shifts in brain structure and spontaneous brain network activity in people living with chronic pain, and it explores how these neural changes connect to reported pain severity and psychological troubles. Methods: This observational, cross-sectional study took place at the department of medicine, Mardan Medical Complex Mardan between January 2022 and January 2023. Seventy-one individuals with chronic pain persisting for more than three months were recruited for the study. Clinical evaluations recorded pain intensity, episode length, and relevant emotional symptoms. Every participant then completed high-resolution structural MRI and resting-state fMRI to assess gray matter volume and functional connectivity, focusing on the default-mode and salience networks. Results: Participants exhibited significant reductions in ‘gray matter volume within the anterior cingulate cortex, prefrontal cortex, and insula compared to healthy controls (p < 0.05)’. Functional connectivity analysis revealed disrupted links between the medial prefrontal cortex and posterior cingulate cortex, and between the insula and prefrontal cortex. ‘A negative correlation was observed between pain intensity and gray matter volume in key regions, suggesting a dose-dependent neural impact’. Conclusion: Chronic pain is associated with both structural and functional brain changes, particularly in regions involved in pain regulation and emotional processing. These findings support a neurobiological model of chronic pain and highlight the importance of early, integrative treatment approaches. Keywords: Chronic pain, brain structure, functional connectivity, ‘gray matter volume, anterior cingulate cortex, prefrontal cortex, resting-state fMRI’